Modification Of Taq DNA Polymerase with Improved Elongation Ability - Sarsen, A.; Akishev, Zh.; Saginova, M.; Sultankulov, B.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2021)
Thermostable polymerases play a significant role in molecular biology and diagnostic practice. The most famous and demanded is Polymerase I from the thermophilic bacterium Thermus aquaticus (Taq-pol). This polymerase at one time made a kind of revolution in the polymerase chain reaction. In this work, we attempted to modify this polymerase by attaching an additional Sso7d protein from Sulfolobus solfataricus to Taq-pol, which provides additional binding to the double-stranded DNA of the template. Sso7d-Taq fusion gene was expressed in BL21(DE3) cells. Optimal conditions were selected for maximum production of modified Sso7d-Taq polymerase. The optimal conditions for the intracellular accumulation of Sso7d-Taq polymerase: activation of the T7 promoter when the optical density of the culture reaches OD600 = 0.8-1.0 by adding IPTG at a concentration of 0.2 mM, followed by incubation of the culture at 37°C for 20-24 hours. Recombinant Sso7d-Taq polymerase has been purified and tested by PCR for thermal stability and elongation time. It was found that the Sso7d-Taq enzyme withstands 5 hour incubation at 95°C and 75 minute incubation at 98°C. Comparative analysis with unmodified Taq DNA polymerase showed that the Sso7d-Taq enzyme reduces the elongation rate by several times - up to 15-13 seconds per 1 kbp. The results obtained indicate the prospects of using Sso7d-Taq DNA polymerase in scientific research and diagnostic practice.